“Efectos de fertilizantes orgánicos sobre el rendimiento del grano en el cultivo de arroz (Oryza sativa L.)” - Fierro Miguez, Stalin Mauricio (2017)
VII. SUMMARY This experimental work was established in the lands of the CEDEGE Irrigation Project owned by Mrs. Lilian Mercedes Pérez Meléndrez, located at Km 12 of the Babahoyo - Montalvo highway, between the geographic coordinates of 790 32`of West longitude and 010 49` 15” south latitude; with a height of 8 m.s.n.m. The zone presents a humid tropical climate, with an average annual temperature of 25.60 ° C; an annual rainfall of 2329.8 mm; relative humidity 82% and 998.2 hours of annual average heliophany. The soil has a flat topography, a loamy clay texture and regular drainage. The research was established in the rice variety 'SFL - 11'. The proposed objectives were to identify the appropriate organic fertilizer to achieve maximum grain yield; determine the agronomic efficiency of organic fertilizers and economically analyze the grain yield according to the cost of production of the treatments. The treatments were constituted by the different doses of organic nutritional fertilizers, such as Fulvex in doses of 1.5 and 2.0 L / ha; Humic Plus dose of 200 and 400 cc / ha and an absolute control (without application). The experimental design of Random Complete Blocks was used, with five treatments and four repetitions. The variables to be evaluated were subjected to the analysis of variance; using Duncan's significance test at 95% probability for comparisons of treatment means. Each experimental plot consisted of dimensions 4.0 m wide x 5.0 m long. The separation between repetitions or block was 1.0 m; there is no separation between the experimental plots. The total area of the trial was 380 m2. All the necessary agricultural work was carried out in the cultivation of rice for its normal development, such as land preparation, sowing, irrigation, fertilization, weed control, phytosanitary control and harvesting. To estimate the effects of the treatments, the following data were taken from days to flowering, plant height, number of tillers and panicles / m2, length of panicles, grains per panicles, weight of 1000 grains, grain yield and economic analysis. Based on the results obtained in the experimental work, it was determined that organic fertilizers influenced the grain yield in rice cultivation a; the absolute control (without application of organic fertilizers) was the treatment that flourished in the longest time; panicle length, number of tillers / m2, panicles / m2 and grains per panicles, stood out with the use of Fulvex in a dose of 2.0 L / ha; the treatment with the organic fertilizer Fulvex in a dose of 2.0 L / ha obtained greater weight of 1000 grains and the highest yield of the crop and net benefit was presented with the use of Fulvex in a dose of 2.0 L / ha with a profit of $ 515,42. Keywords: organic fertilizers, rice, yield, Fulvex, Humic plus.